Extraction of phytochemical from Murraya Koenigii (L.) Spreng leaves using Maceration method / Hana Fareeha Azizuddin ... [et al.] - Azizuddin, Hana Fareeha; Nordin, Nur Farzanah; Saiman, Siti Khadijah; Asman, Saliza; Mohd Idris, Alya Athirah (Research Management Institute (RMI), 2023)
Curry leaves, scientifically known as Murraya koenigii (L.) Spreng is employed as a flavoring agent in a wide range of dishes and possesses the potential for treatment due to its content of flavonoid, steroid, and phenolic compounds. These compounds exhibit antioxidant and antibacterial properties. In this work, the extraction of phytochemicals from M. koenigii leaves was satisfactorily performed. The extraction process was conducted using a maceration technique with three different solvents: 95 % ethanol, 99 % acetone, and 96 % methanol individually. The qualitative and quantitative of existing phytochemicals compounds in the M. koenigii leaves were analyzed through phytochemical screening and gas chromatography-mass spectrometry (GCMS). The percentage yield shows 21.42 % of methanolic extracts, 6.50 % of acetone extracts, and 11.66 % of ethanolic extracts. The major compounds present from screening phytochemicals are terpenoid, phenolic, glycoside, and saponin. GC-MS result showed the major compounds present in M. koenigii leaves are terpene, terpenoid, carotenoid and alkaloid.